Neighbourhood and Community Centres: Results for Children, Families and Communities - Izmir, G; Katz, I; Bruce, J (UNSW Sydney, 2009)
This report is a critical part of the LCSA renewal strategy and it aims to review and synthesise the best evidence available nationally and internationally on how the neighbourhood centres can help improve the wellbeing of children, families and communities and provide a stronger social infrastructure for NSW. The report reviews the literature directly pertinent to neighbourhood and community centres and results, and also research which shows population results arising from neighbourhood and community interventions and the effects of neighbourhoods. It also presents findings on the cost-efficiency of neighbourhood centres. Finally it links these findings to the finding of the Wood Commission and Keeping them Safe, the NSW government’s response to the Commission.
SPRC Report Series 16/09
Keywords: New South Wales; Neighbourhood Centres; Community Centres